Analisa pengaruh putaran spindel pada friction welding terhadap tensile strength Alumunium A6061 - Teuku Haikal Derniawan; Nurdin Nurdin; Fakhriza Fakhriza (Politeknik Negeri Lhokseumawe, 2021)
The welding process using the friction welding method uses friction energy which turns into heat to join two metals. The welding process that occurs on the touch surface of the two metals results in a larger welding area compared to other welding methods where the welding area is only at the contact edge of the metal being joined. With the welding area that is on the entire surface of the joined plane, it allows this type of friction welding joint to accept a greater torsional load, so that in its application friction welding is very suitable for use in the process of joining shafts and metal materials that have circular profiles. The purpose of this study was to determine the effect of spindle rotation on friction welding on the mechanical properties of welding joints on Aluminum 6061 material. Its mechanical properties include a tensile strength test, with variations in spindle rotation on a lathe using 6061 aluminum material. Based on the results of the tensile test at 1500 rpm where the maximum stress on the A1 sempel is 8.88 Kgf/mm2, A2 sempel 8.83 Kgf/mm2 and sempel A3 10,83 Kgf/mm2. And at 2500 rpm where the tensile strength of the B1 sample is 10.73 Kgf/mm2, the B2 sempel is 11.26 Kgf/mm2 and the B3 sempel is 8.20 Kgf/mm2. From the results of the tensile test, it was obtained that the strength of the 6061 Aluminium joint by the friction welding method was the highest yield strength of 5.8 kg/mm2 and a maximum tensile strength of 11.26 kg/mm2, and the raw material tensile strength was 12.6 kgf/mm2, the tensile strength of raw material and material after friction welding differs only slightly